The effectiveness of advertising campaign for student discipline problems at school in Malaysia / Norhaniza Mohamad - Mohamad, Norhaniza (Faculty of Art and Design, 2013)
Discipline can be defined as to follow a particular rule of conduct or order. Discipline also means a systematic instruction given to train the students in school. Disciplines in school are the rules that they should follow to control their actions and attitudes in school through fine and punishments if they did something wrong. Discipline problem in school today has become hot news discussed. Sometimes it not only involves the school, Ministry of Education, but also involves the police in taking action against the students because the problem is not just a small problem, but there is already beyond the crime problem. Basically, discipline problems occur when a student refuses to obey rules of the classroom or school.The purpose of this study is to give awareness to the society about the importance of discipline in school. It is to make them realized about how the discipline affects the children’s future. The researcher distributed online survey through emails and social networking for the people to gain more information about this matter. The first chapter will discuss about the background research. The background research will tell about the discipline problems among students in Malaysia as well as to describe about the campaign. Problem statement will follow in order as to state the unsolved problems about this study. There are also the objective of the research, hypothesis, limitation, delimitation and significance of this study. Literature review would reveal on some articles and issues about discipline problems in school as well as some quotes from those who are expert in the field of study to strengthen this research